2010
DOI: 10.1038/ng.525
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping identifies multiple loci for a canine SLE-related disease complex

Abstract: The unique canine breed structure makes dogs an excellent model for studying genetic diseases. Within a dog breed, linkage disequilibrium is extensive, enabling genome-wide association (GWA) with only around 15,000 SNPs and fewer individuals than in human studies. Incidences of specific diseases are elevated in different breeds, indicating that a few genetic risk factors might have accumulated through drift or selective breeding. In this study, a GWA study with 81 affected dogs (cases) and 57 controls from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 26 publications
1
84
0
2
Order By: Relevance
“…Fine-mapping of the associated genomic regions and high throughput sequencing experiments to find the causative genes and mutations are ongoing. Even if it may take some time to identify the actual causative mutations and/or precise molecular mechanisms leading to disease (especially when dealing with regulatory mutations), identifying the causative genes or pathways, which is relatively easier, may on its own pave the way for the investigation of similar pathways in the corresponding human disorders (Wilbe et al, 2010), as well as for the identification of novel drug targets. Personalised medicine for dogs, based on the genes and pathways underlying the development of specific disorders, may be a future possibility for veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Fine-mapping of the associated genomic regions and high throughput sequencing experiments to find the causative genes and mutations are ongoing. Even if it may take some time to identify the actual causative mutations and/or precise molecular mechanisms leading to disease (especially when dealing with regulatory mutations), identifying the causative genes or pathways, which is relatively easier, may on its own pave the way for the investigation of similar pathways in the corresponding human disorders (Wilbe et al, 2010), as well as for the identification of novel drug targets. Personalised medicine for dogs, based on the genes and pathways underlying the development of specific disorders, may be a future possibility for veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some susceptible breeds may have a higher incidence of more than one immune-mediated disease (Day and Penhale 1992;Day 1996;Wilbe et al 2010). The recognition of foreign proteins or selfproteins by the major histocompatibility complex (MHC) proteins is one of the key events in the development of immune-mediated disease (McDevitt 2000).…”
Section: Breed and Sex Predispositionmentioning
confidence: 99%
“…Dogs have previously been proven useful in determining predisposing genetic markers for human diseases due to the breed structure caused by artificial breeding for phenotypic factors (Dodman et al 2010;Wilbe et al 2010;Shearin et al 2012;Karlsson et al 2013;Tang et al 2014). A recent lymphoma study in dogs identified a gene (TRAF3) as being commonly mutated in both dog and human B-cell lymphomas (Bushell et al 2015).…”
mentioning
confidence: 99%